Teaching English to Students with Autism Spectrum Disorder (ASD) - Maysuroh, Siti; Dwimaulani, Astrid; Wati, Laila; Nurhayati, Nurhayati; Yusri, Nurul (Journey: Journal of English Language and Pedagogy, 2024)
Students with autism spectrum disorder (ASD) typically show a unique pattern in their language learning. This fact has been documented in a number of earlier investigations. However, it was discovered that Indonesian teachers and educational institutions were insufficiently prepared to fulfill the needs of their students, both in terms of teaching strategies and the material development. This study then aimed at examining appropriate strategies of teaching English to ASD students as well as finding out the challenges faced by teacher in teaching English in the classroom. The research design of this study was case study research with qualitative approach. The participant of this study was English teacher at SLBN 01 Lombok Timur chosen using purposive sampling. The researchers used documentation, in-depth interviews, and observation to acquire data. The results revealed that the teacher faced some challenges in teaching ASD students, such as lack of focus and concentration during teaching and learning process and speech delay. To address these issues, the teacher and school principle used some strategies to teach children with autism, namely developing oral language comprehension and developing lesson plan with visual media to help the student learn English as a foreign language